Assessment of the Effect of Deleting the African Swine Fever Virus Gene R298L on Virus Replication and Virulence of the Georgia2010 Isolate - Elizabeth Ramirez-Medina; Lauro Velazquez-Salinas; Alyssa Valladares; Ediane Silva; Leeanna Burton; Douglas P. Gladue; Manuel V. Borca (Viruses)
African swine fever (ASF) is a lethal disease of domestic pigs that is currently challenging swine production in large areas of Eurasia. The causative agent, ASF virus (ASFV), is a large, double-stranded and structurally complex virus. The ASFV genome encodes for more than 160 proteins; however, the functions of most of these proteins are still in the process of being characterized. The ASF gene R298L, which has previously been characterized as able to encode a functional serine protein kinase, is expressed late in the virus infection cycle and may be part of the virus particle. There is no description of the importance of the R298L gene in basic virus functions such as replication or virulence in the natural host. Based on its evolution, it is proposed that there are four different phenotypes of R298L of ASFV in nature, which may have potential implications for R298L functionality. We report here that a recombinant virus lacking the R298L gene in the Georgia 2010 isolate, ASFV-G-∆R298L, does not exhibit significant changes in its replication in primary cultures of swine macrophages. In addition, when experimentally inoculated in pigs, ASFV-G-∆R298L induced a fatal form of the disease similar to that caused by the parental virulent ASFV-G. Therefore, deletion of R298L does not significantly affect virus replication and virulence in domestic pigs of the ASFV Georgia 2010 isolate.